The Morality of Freedom. - Raz, Joseph (Oxford University Press, UK, 1986)
Winner of the W.J.M. Mackenzie Prize of the Political Studies Association for 1987. Intro – Acknowledgements – Contents – 1. THE PROBLEM OF POLITICAL FREEDOM – 1. A Journey of Exploration – 2. The Importance of Politics – 3. The Revisionist Challenge – 4. The Presumption of Liberty – 5. The Simple Principle – 6. The Inadequacy of Linguistic Analysis – 7. Liberalism and Individualism – I. The Bounds of Authority – 2. AUTHORITY AND REASON – 1. Authority and Justified Power – 2. The Recognitional Conception – 3. The Inspirational Conception – 4. Content-Independent Reasons – 3. THE JUSTIFICATION OF AUTHORITY – 1. 'Surrendering One's Judgement' – 2. The Dependence Thesis – 3. The Justification of Authority – 4. The Pre-emptive Thesis – 5. Objections – 4. THE AUTHORITY OF STATES – 1. The Normal Justification of Political Authority – 2. Consent – 3. Consent as the Foundation of Authority – 4. Respect for Law – 5. The Political Obligation – II. Anti-Perfectionism – 5. NEUTRAL POLITICAL CONCERN – 1. Forms of Neutrality – 2. The Impossibility of Strict Political Neutrality – 3. Neutrality and the Social Role of Justice – 4. From Neutrality to Pluralism – 6. THE EXCLUSION OF IDEALS – 1. Preliminaries – 2. Political Welfarism – 3. Treating People as Ends – 4. Coercion and Autonomy – 5. On Some Underlying Intuitions – III. Individualistic Freedom: Liberty and Rights – 7. THE NATURE OF RIGHTS – 1. Rights: The Main Features – 2. Core and Derivative Rights – 3. The Correlativity of Rights and Duties – 4. Holding Individuals to be Under a Duty – 5. Promises and Agreements – 6. Capacity for Rights – 7. Rights and Interests – 8. Rights and Duties – 9. The Importance of Rights – 8. RIGHT-BASED MORALITIES – 1. Some Preliminary Doubts – 2. Rights and Individualism – 3. Autonomy and Rights – 4. Collective Rights – 5. Intrinsic Duties – 6. Rights and Narrow Morality – 9. EQUALITY.
Description based on publisher supplied metadata and other sources
Keywords: Authority; Liberty; Electronic books